Pregunta
upstudy study bank question image url

3. Use the distributive property to show that the equations are equal. Examples: \( a(b+c)=a \times b+a \times c \) \[ \begin{array}{l} a\left(b^{2}+c^{2}\right)=a \times b^{2}+a \times c^{2} \\ a(b-c)=a \times b-a \times c \\ a\left(b^{2}-c^{2}\right)=a \times b^{2}-a \times c^{2} \end{array} \] a. \( \left(b^{2}+c^{3}\right) d= \) b. \( c\left(b+d^{2}\right)= \) c. \( \left(b^{2}+d^{2}\right) \times c= \) E \( \square \) d. \( d \times\left(c+b^{2}\right)= \) e. \( \left(d^{2} \times b^{3}\right)+\left(d^{2} \times c^{3}\right)= \)

Ask by Rojas Barnett. in South Africa
Feb 18,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

\[ \begin{array}{l} a. \ (b^{2}+c^{3}) d = b^{2}d + c^{3}d \\ b. \ c(b+d^{2}) = cb + cd^{2} \\ c. \ (b^{2}+d^{2}) \times c = b^{2}c + d^{2}c \\ d. \ d \times (c+b^{2}) = dc + db^{2} \\ e. \ (d^{2} \times b^{3}) + (d^{2} \times c^{3}) = d^{2}(b^{3} + c^{3}) \end{array} \]

Solución

To show that the equations are equal using the distributive property, we will apply the property step by step for each expression provided. The distributive property states that \( a(b+c) = ab + ac \). Let's go through each part: ### a. \( (b^{2}+c^{3}) d \) Using the distributive property: \[ (b^{2}+c^{3}) d = b^{2}d + c^{3}d \] ### b. \( c(b+d^{2}) \) Using the distributive property: \[ c(b+d^{2}) = cb + cd^{2} \] ### c. \( (b^{2}+d^{2}) \times c \) Using the distributive property: \[ (b^{2}+d^{2}) \times c = b^{2}c + d^{2}c \] ### d. \( d \times (c+b^{2}) \) Using the distributive property: \[ d \times (c+b^{2}) = dc + db^{2} \] ### e. \( (d^{2} \times b^{3}) + (d^{2} \times c^{3}) \) This expression can be factored using the distributive property: \[ d^{2} \times b^{3} + d^{2} \times c^{3} = d^{2}(b^{3} + c^{3}) \] ### Summary of Results 1. \( (b^{2}+c^{3}) d = b^{2}d + c^{3}d \) 2. \( c(b+d^{2}) = cb + cd^{2} \) 3. \( (b^{2}+d^{2}) \times c = b^{2}c + d^{2}c \) 4. \( d \times (c+b^{2}) = dc + db^{2} \) 5. \( (d^{2} \times b^{3}) + (d^{2} \times c^{3}) = d^{2}(b^{3} + c^{3}) \) Each expression has been simplified using the distributive property, demonstrating that they are equal to their respective expanded forms.

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Mind Expander

To demonstrate the use of the distributive property for the given scenarios: a. \( \left(b^{2}+c^{3}\right) d = b^{2}d + c^{3}d \) b. \( c\left(b+d^{2}\right) = cb + cd^{2} \) c. \( \left(b^{2}+d^{2}\right) \times c = b^{2}c + d^{2}c \) d. \( d \times\left(c+b^{2}\right) = dc + db^{2} \) e. \( \left(d^{2} \times b^{3}\right)+\left(d^{2} \times c^{3}\right) = d^{2}(b^{3} + c^{3}) \) This property allows you to factor out a common term, making it easier to manipulate complex expressions!

Latest Algebra Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad